EVALUATION OF ANTIOXIDANT ACTIVITY OF SAPONIN AND TANNIN FRACTIONS ISOLATED FROM THE LEAVES OF TRIDAX PROCUMBENS - P. S. PANDE; V. D. MANE; M. N. MISHRA (International Journal of Pharma and Bio Sciences, 2014)
Saponin and tannin fractions have been isolated from the leaves of tridax procumbens. The quantitative evaluation of antioxidant activity was elucidated. Both fractions showed moderate to good antioxidant activity assay for DPPH. IC50 values of both fractions have also been reported in the study.